On H-Irregularity Strength of Grid Graphs - Meilin Imelda Tilukay (Tensor: Pure and Applied Mathematics Journal, 2020)
This paper deals with three graph characteristics related to graph covering named the (vertex, edge, and total, resp.) –irregularity strength of a graph admitting -covering. Those are the minimum values of positive integer such that has an -irregular (vertex, edge, and total, resp.) -labeling. The exact values of this three graph characteristics are determined for grid graph admitting grid-covering,